Institute of Medical Ethics Guidelines for confirmation of appointment, promotion and recognition of UK bioethics and medical ethics researchers. Issue 5 (23rd March 2018) - Frith, Lucy; Hooper, Carwyn; Camporesi, Silvia; Douglas, Thomas; Smajdor, Anna; Nottingham, Emma; Fritz, Zoe; Ekberg, Merryn; Huxtable, Richard
Abstract : This document is designed to give guidance on assessing researchers in bioethics/medical ethics. It is intended to assist members of selection, confirmation and promotion committees, who are required to assess those conducting bioethics research when they are not from a similar disciplinary background. It does not attempt to give guidance on the quality of bioethics research, as this is a matter for peer assessment. Rather it aims to give an indication of the type, scope and amount of research that is the expected in this field. It does not cover the assessment of other activities such as teaching, policy work, clinical ethics consultation and so on, but these will be mentioned for additional context. Although it mentions the UK's Research Excellence Framework (REF), it is not intended to be a detailed analysis of the place of bioethics in the REF.